A Comparative Study of Strategies Adopted by Wal-Mart and Carrefour in China: A Resource-Based Perspective - LIU, YUE (2007)
This research aims to provide an overview of links between a firm's strategies and the firm possessed resources and capabilities. Two cases Ã¢ÂÂWal-Mart and Carrefour in China are chosen. By using resources-based theory, their development strategies in China are compared and analyzed. This research adopted documentary research method, particularly firms historical documentary review and analysis, for this qualitative research to study each case.